As (d)eficiências na gestão de bibliotecas universitárias: um olhar sobre a perspectiva da diversidade - Michelle Karina Assunção Costa (2022)
Brazil has a set of laws aimed at the rights of people with disabilities recognized as one of the most comprehensive in the world. And it is observed in higher education, a growth over the years in the number of enrollments of these people. Considering these indicator data for university library management, the present investigation has the general objective of analyzing the management of the Library Systems of the Pontifical Catholic University of Minas Gerais (PUC Minas) and the Federal University of Minas Gerais (UFMG) from the perspective of the diversity of users to access to information and inclusion in the university library. With the consequences of identifying in the collection development policy, user guide, regulation and other normative documents aspects that cover the dimensions of accessibility, formation of accessible collection, assistive technologies, users with disabilities, among other correlates; verify whether user studies are carried out and whether they include aspects of accessibility and inclusion; verify whether guidelines from the matrix of reference documents for accessibility, inclusion and rights of PWD are implemented in library systems; to know the perception of the Deans of Higher Education Institutions the Pro-Rectors of Graduation, the Coordinators of the Inclusion Centers of the Universities, the Managers of the University Library Systems, the Librarians in the leadership/coordination role on accessibility and inclusion of users with disabilities in the university library; to know the perception of users with disabilities regarding access to information and use of the library. A descriptive, exploratory research with a qualitative approach was carried out through a comparative study. The empirical research was carried out with documental research, consulting the websites of the Library Systems, applying an electronic questionnaire and semi-structured interview on-line via Google Meet. The intentional sample consisted of seven managers, 33 librarian managers and 35 students with disabilities. The Contingency Theory, Reference Documents Matrix and Bardin's Content Analysis Technique were used to analyze the collected data. Among the results, the proposed objectives were achieved, they demonstrate that the inequalities in the university library towards users with disabilities remain and this theme is incipient in the management documents, making it difficult to create an inclusive culture. In both systems, the Communication Barrier, the Furniture and Equipment Barrier and the Architectural/Physical Barrier were mentioned, being the barriers present in the daily life of the university library for the disabled user. Librarians at PUC Minas had fewer difficulties in serving this public than those at UFMG. And all PUC Minas librarians have already assisted people with disabilities while at UFMG, 14.3% of the sample said they had never assisted this public. Managers have more knowledge with the theme and experience with this public than coordinating librarians. Students who declared themselves with physical, intellectual, low vision, autism spectrum disorder, deafness, modular blindness, monocular vision, Attention Deficit Hyperactivity Disorder, cognitive overload and cognitive inhibition and Irlen participated. Of this sample, 53.8% said that they partially receive the same conditions of care, attention, and equal access compared to users without disabilities.